2008
DOI: 10.1007/s11422-008-9103-3
|View full text |Cite
|
Sign up to set email alerts
|

“Who polluted the Potomac?” The translation and implementation of a US environmental story in Brazilian and Turkish classrooms

Abstract: In this study we examine how elementary teachers in Brazil and Turkey approached the translation and subsequent classroom implementation of an instructional activity that promotes environmental awareness through a combination of student role playing and teacher oral delivery of an environmental story about river pollution. A discourse analysis showed that translation into Portuguese was literal, an approach that fostered a classroom implementation that emphasized detached transmission of knowledge (the teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Because some English words and grammatical structures lacked a precise equivalent in the target language, adaptations such as replacements, deletions, additions, and structural changes were repeatedly needed. This finding supports the contention that translating a text is more than simply establishing semantic equivalence (i.e., unproblematically and directly finding equivalent words, phrases, and texts in a target language; Oliveira, Colak, & Akerson, 2009). When a written text is transferred to another language, the translator has to transpose not only referential meanings (the literal message of the text) but also more problematic nonliteral meanings that often require a degree of free translation (adaptation of the linguistic message).…”
Section: Translation In Mathematics Discussionsupporting
confidence: 73%
“…Because some English words and grammatical structures lacked a precise equivalent in the target language, adaptations such as replacements, deletions, additions, and structural changes were repeatedly needed. This finding supports the contention that translating a text is more than simply establishing semantic equivalence (i.e., unproblematically and directly finding equivalent words, phrases, and texts in a target language; Oliveira, Colak, & Akerson, 2009). When a written text is transferred to another language, the translator has to transpose not only referential meanings (the literal message of the text) but also more problematic nonliteral meanings that often require a degree of free translation (adaptation of the linguistic message).…”
Section: Translation In Mathematics Discussionsupporting
confidence: 73%
“…In particular, like Beaton et al (2000), we found that the use of back-translation was very useful in identifying translation difficulties. Further research into this important approach to analysing the quality of translated texts is crucial if we are to encourage the adoption of the most efficient translation practices and promote effective scientific instruction worldwide (Oliveira, Colak, & Akerson, 2009). Although there are many online resources that allow for quick translation, these services often employ only literal translation techniques, paying little attention to context or cultural meaning.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, translation into Portuguese was literal, that is, without any significant alterations to the referential contents of the original dilemma cards. For a more information about the curriculum translation process and its implementation, see Oliveira, Colak, and Akerson (2009a, 2009b) and Oliveira and Dhingra (2008).…”
Section: Methodsmentioning
confidence: 99%